Rancang Bangun Sistem Informasi Pencatatan dan Pengelolaan Data Pekerjaan Karyawan di PT Aplic Digital Teknologi - Setiawan, Topan (INTERNAL (Information System Journal), 2024)
The design and development of an information system for recording and managing employee work data aim to simplify the process of tracking and monitoring employee tasks, including when tasks are assigned and when they are expected to be completed. This system is designed to replace manual administrative processes, enabling work-related information to be accessed more quickly and accurately. The method used is System Development Life Cycle (SDLC) with system development using a waterfall method approach which involves the stages of needs analysis, design, design, and implementation. With this system, management can regularly monitor the progress of employee tasks and evaluate the efficiency of task completion. Additionally, the system records work history, which can be used for reporting and further analysis. The implementation results show that the system improves the accuracy of work data recording and supports more effective decision-making.